Refresentatif Kode Hermeunotik pada Film “1 Kakak 7 Ponakan” (Analisis Studi Semiotika Roland Barthes) - Muhammad Yusuf Yunus; Lilis Suryani; Kurnia Kurnia; Alia Alia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This study aims to identify the forms of semiotic lexical meaning in the hermeneutic code aspect in Roland Barthes' view, in addition to the use of codes to reveal the meaning in the film, the researcher analyzes the moral message in the film